Eponyms - As Onomastic Unit - Makhsudova Holiskhon Ummatovna; Shakhobiddinova Shokhida Hoshimovna (Central Asian Journal of Theoretical and Applied Science, 2022)
This article examines the role and importance of the concept of onomastic units in lexicology, the field terminology, giving a new meaning to existing onomastic units and increasing the vocabulary of a particular language - the study of eponyms.